Assessing and comparing Functional outcome in Olecranon fracture managed by tension band wiring and transcortical screw fixation - Shankar S; Abdul Rasheem PT; Saj Sreejesh (International Journal of Health and Clinical Research, 2021)
Background: Olecranon fractures typically involve the articular surface of the elbow. Plate and screw fixation is recommended for unstable fracture patterns with significant comminution or a fracture line exiting distal to the semilunar notch (Mayo Type 2B) and fracture-dislocations (Mayo Type 3). Intramedullary nails are now available and may be suitable for some fracture types. Intramedullary devices may avoid the wound complications related to the superficial location of traditional hardware used to treat olecranon fractures.The present study was undertaken for assessing and comparing Functional outcome in Olecranon fracture managed by tension band wiring and transcortical screw fixation. Materials & methods:This prospective randomized study was conducted on 30 patients with olecranon fractures. All the patients were broadly divided into two study groups: Group 1 and Group 2. Group 1 patients were managed by Tension band wiring and Group 2 patients were managed by Transcortical screw fixation. Initial follow up was done at 1, 4 and 6 weeks after discharge and all patients were followed up for 6 months. Radiological, clinical and functional assessment was done using Mayo Elbow Performance Score. Results: Mean duration of surgery among the patients of the tension band wiring group and transcortical screw fixation group was 38.4 minutes and 48.1 minutes respectively. Mean range of motion on follow-up among the patients of the tension band wiring group and transcortical screw fixation group was 103.1° and 102.1° respectively. Mean time for complete union among the patients of the tension band wiring group and Transcortical Screw Fixation group was 11.58 weeks and 11.47 weeks respectively. Non-significant results were obtained while comparing the outcome among the patients of both the study groups. Conclusion: Tension band wiring is better than transcortical screw fixation in terms of duration of surgery. At the same time, tension band wiring has higher chances of development of superficial infection in comparison to transcortical screw fixation.